2022
DOI: 10.1186/s12891-022-06060-8
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive trans-superior articular process percutaneous endoscopic lumbar discectomy with robot assistance

Abstract: Background To compare the clinical outcomes of patients with lumbar disc herniation treated with robot-assisted percutaneous endoscopic lumbar discectomy (r-PELD) or conventional PELD under fluoroscopy guidance (f-PELD). Methods Our study group included 55 patients, 22 in the r-PELD group and 33 in the f-PELD group. The following clinical and surgical outcomes were compared between the two groups: the visual analog scale for radiculopathy pain; Osw… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Robot-assisted spine surgery can provide accurate and safe guidance for discography in the initial steps of percutaneous endoscopic cervical discectomy or PELD [ 125 , 126 ]. Robot assistance was recently used to perform full endoscopic lumbar discectomy [ 127 ]. Thus, robot-assisted surgery may be used to perform other techniques of spine endoscopy in the near future.…”
Section: Latest Advancesmentioning
confidence: 99%
“…Robot-assisted spine surgery can provide accurate and safe guidance for discography in the initial steps of percutaneous endoscopic cervical discectomy or PELD [ 125 , 126 ]. Robot assistance was recently used to perform full endoscopic lumbar discectomy [ 127 ]. Thus, robot-assisted surgery may be used to perform other techniques of spine endoscopy in the near future.…”
Section: Latest Advancesmentioning
confidence: 99%
“…Similarly, robotic-endoscopic applications appear to provide favorable results at present; however, these studies are limited to very small sample sizes and retrospective studies. Specifically, Wang et al found that robot use in endoscopic lumbar discectomy was associated with less intraoperative blood and similar complication profile [81]. Further study is certainly required to describe this robotic application more completely.…”
Section: Endoscopymentioning
confidence: 99%
“…Robot-assisted spine surgery can provide accurate and safe guidance for discography in the initial steps of percutaneous endoscopic cervical discectomy (113) or PELD (114). Robot assistance was recently used to perform full endoscopic lumbar discectomy (115). Thus, robot assisted surgery may be used to perform other techniques of spine endoscopy in the near future.…”
Section: Robot-assisted Endoscopic Surgerymentioning
confidence: 99%